Efficient Economic Rent Taxation under a Global Minimum Corporate Tax - Shafik Hebous; Andualem Mengistu (CESifo GmbH, 2024)
The international agreement on a corporate minimum tax is a milestone in global corporate tax arrangements. The minimum tax disturbs the equivalence between otherwise equivalent forms of efficient economic rent taxation: cash-flow tax and allowance for corporate equity. The marginal effective tax rate initially declines as the statutory tax rate rises, reaching zero where the minimum tax is inapplicable, and increases thereafter. This kink occurs at a lower statutory rate under cash-flow taxation. We relax the assumption of full loss offset; provide a routine for computing effective rates under different designs; and discuss policy implications of the minimum tax.
Keywords: H21; H25; F23; 330; investment; minimum taxation; corporate tax reform; international taxation; rent tax